Potassium Application Boosts Photosynthesis and Sorbitol Biosynthesis and Accelerates Cold Acclimation of Common Plantain (Plantago major L.) - Ho, Li-Hsuan (Plants (Basel), 2020)
Potassium (K) is essential for the processes critical for plant performance, including photosynthesis, carbon assimilation, and response to stress. K also influences translocation of sugars in the phloem and regulates sucrose metabolism. Several plant species synthesize polyols and transport these sugar alcohols from source to sink tissues. Limited knowledge exists about the involvement of K in the above processes in polyol-translocating plants. We, therefore, studied K effects in Plantago major, a species that accumulates the polyol sorbitol to high concentrations. We grew P. major plants on soil substrate adjusted to low-, medium-, or high-potassium conditions. We found that biomass, seed yield, and leaf tissue K contents increased in a soil K-dependent manner. K gradually increased the photosynthetic efficiency and decreased the non-photochemical quenching. Concomitantly, sorbitol levels and sorbitol to sucrose ratio in leaves and phloem sap increased in a K-dependent manner. K supply also fostered plant cold acclimation. High soil K levels mitigated loss of water from leaves in the cold and supported cold-dependent sugar and sorbitol accumulation. We hypothesize that with increased K nutrition, P. major preferentially channels photosynthesis-derived electrons into sorbitol biosynthesis and that this increased sorbitol is supportive for sink development and as a protective solute, during abiotic stress.